Penentuan Lokasi dan Perancangan Tata Letak Fasilitas Tempat Packaging PT.ABC - Rubianto, Christina Natalia; Bendatu, Liem Yenny (Jurnal Titra, 2014)
PT. ABC is a company that sells cooking oil in a bulk size, however the company is willing to develop their new efficient packaging in 18L jerry-can. The company wants to determine the right location for the packaging location and also designs departmentsâ layout inside. The chosen location is âLocation Kâ. The facility layout design is done using ALDEP, CORELAP, CRAFT methods. The result after adjustment shows the best option is using CORELAP with the momen of 7100.